ชุมชนเสมือนของกลุ่มวัฒนธรรมฟุตบอลในกระดานข่าวอิเล็กทรอนิกส์ - ธนภูมิ เรืองวิทยานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To focuse on the role of the Constitutional Court on the Performance of the Election Commission. The powers and duties of the Constitutional court and the Election Commission are as the constitutional organs established by the Constitution. The study reveals that many constitutional organs are established by the Constitution of the Kingdom of Thailand B.E. 2540 . The constitutional organs will exercise the power to examine the State organs. The State organs consist of the organizations of the courts and non-organization of the court. The suggestion is based on the principle of restrictive interpretation of the Constitution. Since the jurisdiction of the Constitutional Court is restricted only as specified by the law, the provisions of the Constitution should not be interpreted to expand it. As for the problem of what court should have the jurisdiction over the rules and regulations of the constitutional organizations, we conclude that they fall within the jurisdiction of the Administrative Court rather than that of the Constitutional Court. If they are interpreted to be within the powers of the Constitutional court, its jurisdiction will become broader than that specified by the Constitution. As for the issue of the exercise of the powers and duties of the Constitutional Court in relation to the Election Commission, the thesis recommends that the Constitutional court should really put the limit on itself not to interfere the powers of constitutional organizations. This is because the Constitutional Court has not obtained the proper status for doing that. The thesis makes the final conclusion that the restrictive interpretation of the Constitutional Court will push it to actaually serve as the proper autonomous organization, and ultimately, will bring about precedents for future cases.